2015
DOI: 10.3168/jds.2014-8143
|View full text |Cite
|
Sign up to set email alerts
|

Colostrum protein uptake in neonatal lambs examined by descriptive and quantitative liquid chromatography-tandem mass spectrometry

Abstract: Colostrum intake is a key factor for newborn ruminant survival because the placenta does not allow the transfer of immune components. Therefore, newborn ruminants depend entirely on passive immunity transfer from the mother to the neonate, through the suckling of colostrum. Understanding the importance of specific colostrum proteins has gained significant attention in recent years. However, proteomics studies of sheep colostrum and their uptake in neonate lambs has not yet been presented. The aim of this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 74 publications
1
29
1
Order By: Relevance
“…In agreement with this, in the current experiment, protein and fat percentages decreased and the lactose percentage increased from partum to 10 d of lactation. However, once colostrum production ceased, the milk composition was almost constant over time because the mammary gland developed a high tolerance to external factors, mainly diet [30,31], over the course of evolution to preserve functions and ensure the survival of the newborn ruminants [32]. In addition, this resilience is extendable to the fatty acid composition [33].…”
Section: Milkmentioning
confidence: 99%
“…In agreement with this, in the current experiment, protein and fat percentages decreased and the lactose percentage increased from partum to 10 d of lactation. However, once colostrum production ceased, the milk composition was almost constant over time because the mammary gland developed a high tolerance to external factors, mainly diet [30,31], over the course of evolution to preserve functions and ensure the survival of the newborn ruminants [32]. In addition, this resilience is extendable to the fatty acid composition [33].…”
Section: Milkmentioning
confidence: 99%
“…Several studies have been previously reported, focusing primarily on the genome and on gene functions, nevertheless a growing number of the so-called post-genomics tools (Proteomics, Lipidomics, Metabolomics and Transcriptomics) have been playing an important role in understanding how biological systems work and interact. In particular, proteomics has been found to have a major role, not just in animal selection, but in diverse areas of animal and veterinary sciences [ 16 ][ 17 ] such as meat sciences [ 18 ][ 19 ], colostrum uptake [ 20 ][ 21 ][ 22 ] or the study of specific diseases such as chronic kidney disease in cats [ 23 ]. In fact, and although farm animal species poses some limitations [ 24 ], it is clear that significant results have been achieved in species such as cattle [ 25 ], rabbit [ 26 ] and pig [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although the transfer of immunoglobulins (IgG and IgM, mainly) is a key factor for host defense against pathogens, a wider range of colostrum components, such as the complement system proteins, have been suggested to contribute to the early protection of the neonate (Smith and Foster, 2007;Hernández-Castellano et al, 2015a). The complement system activity -comprising the total (TCA) and alternative (ACA) pathways -plays an important role in host defense mechanisms against infectious microbes, because it is involved in specific and non-specific immunity (Rodríguez et al, 2009;Hernández-Castellano et al, 2015b).…”
Section: Introductionmentioning
confidence: 99%
“…No references about the amount of colostrum required by newborn lambs reared under artificial conditions have been found. As it is essential to obtain adequate immunoglobulin concentrations in the blood (O'Doherty and Crosby, 1997;Quigley et al, 2000;Christley et al, 2003), this knowledge has high relevance for the survival of the lambs.Although the transfer of immunoglobulins (IgG and IgM, mainly) is a key factor for host defense against pathogens, a wider range of colostrum components, such as the complement system proteins, have been suggested to contribute to the early protection of the neonate (Smith and Foster, 2007;Hernández-Castellano et al, 2015a). The complement system activity -comprising the total (TCA) and alternative (ACA) pathways -plays an important role in host defense mechanisms against infectious microbes, because it is involved in specific and non-specific immunity (Rodríguez et al, 2009;Hernández-Castellano et al, 2015b).…”
mentioning
confidence: 99%